Progress on the Studies of the Key Enzymes of Ginsenoside Biosynthesis - Jin-Ling Yang; Zong-Feng Hu; Ting-Ting Zhang; An-Di Gu; Ting Gong; Ping Zhu (Molecules, 2018)
As the main bioactive constituents of Panax species, ginsenosides possess a wide range of notable medicinal effects such as anti-cancer, anti-oxidative, antiaging, anti-inflammatory, anti-apoptotic and neuroprotective activities. However, the increasing medical demand for ginsenosides cannot be met due to the limited resource of Panax species and the low contents of ginsenosides. In recent years, biotechnological approaches have been utilized to increase the production of ginsenosides by regulating the key enzymes of ginsenoside biosynthesis, while synthetic biology strategies have been adopted to produce ginsenosides by introducing these genes into yeast. This review summarizes the latest research progress on cloning and functional characterization of key genes dedicated to the production of ginsenosides, which not only lays the foundation for their application in plant engineering, but also provides the building blocks for the production of ginsenosides by synthetic biology.